1992
DOI: 10.2527/1992.7051404x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant porcine somatotropin for sows during late gestation and throughout lactation

Abstract: Two experiments were conducted to evaluate whether administration of recombinant porcine somatotropin (pST) to sows (Hampshire-Yorkshire) enhanced lactational performance. In Exp. 1, sows (n = 84) were fed a corn-soybean meal diet (17.8% CP), or a similar diet with 8% added fat, from d 108 of gestation to d 28 of lactation. Half of the sows fed each diet were injected with 6 mg/d of pST from d 108 of gestation to d 24 of lactation. Diets were fed at 2.27 kg/d from d 108 of gestation until farrowing and then we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
3
7
0
2
Order By: Relevance
“…However, weight gain was associated with back fat loss in the latter group. These changes were previously reported in other studies and may be explained by the repartitioning effect of rpST (energy from fat to muscle) observed in growingfinishing pigs and in ST-treated sows (Cromwell et al 1992, Rehfeldt et al 2001.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, weight gain was associated with back fat loss in the latter group. These changes were previously reported in other studies and may be explained by the repartitioning effect of rpST (energy from fat to muscle) observed in growingfinishing pigs and in ST-treated sows (Cromwell et al 1992, Rehfeldt et al 2001.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies evaluating rpST administration during pregnancy have observed a certain number of deaths in sows before and during parturition and lactation (Smith et al 1991, Cromwell et al 1992. The mortality seems to be dose-related, with death rates of 0, 6, 26 and 100% in sows injected with 0, 4, 8 and 16 mg rpST respectively (Smith et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, bovine ST (bST) is a potent stimulator of milk production in cows (Etherton and Bauman, 1998), however, the effect of porcine ST (pST) on lactation performance in swine is equivocal. Most (Cromwell et al, 1992;Toner et al, 1996), but not all (Harkins et al, 1989) studies, have shown little effect of exogenous pST on milk production in swine. Inhibition of GH secretion by immuno-neutralization of GH releasing factor, reduced serum IGF-I concentrations by 50% and milk production on d21 of lactation by 32% in swine, however, milk composition and piglet weight at weaning were unaffected, leading the authors to conclude that pST facilitates, but is not essential for lactation in swine (Armstrong et al, 1994).…”
Section: Discussionmentioning
confidence: 97%
“…Vários autores registraram valores para peso corporal antes do parto (AZAIN, 1993;CROMWELL, et. al., 1992;LI e HACKER, 1995;SCHOENHERR et.…”
Section: Mudanças Corporaisunclassified
“…Em contrapartida foram apresentados valores para as perdas de peso, referentes ao período lactacional, mais elevados do que os encontrados na literatura (BABINSZKY, et. al., 1992b;CROMWELL et. al.,1992;LI e HACKER, 1995;SCHOENHERR et.…”
Section: Mudanças Corporaisunclassified